Common Variants at Putative Regulatory Sites of the Tissue Nonspecific Alkaline Phosphatase Gene Influence Circulating Pyridoxal 5′-Phosphate Concentration in Healthy Adults. Issue 7 (13th May 2015) - Carter, Tonia C; Pangilinan, Faith; Molloy, Anne M; Fan, Ruzong; Wang, Yifan; Shane, Barry; Gibney, Eileen R; Midttun, Øivind; Ueland, Per M; Cropp, Cheryl D; Kim, Yoonhee; Wilson, Alexander F; et al.
Abstract: Background: Vitamin B-6 interconversion enzymes are important for supplying pyridoxal 5′-phosphate (PLP), the co-enzyme form, to tissues. Variants in the genes for these enzymes [tissue nonspecific alkaline phosphatase ( ALPL ), pyridoxamine 5′-phosphate oxidase, pyridoxal kinase, and pyridoxal phosphatase] could affect enzyme function and vitamin B-6 status. Objectives: We tested whether single-nucleotide polymorphisms (SNPs) in these genes influence vitamin B-6 status markers [plasma PLP, pyridoxal (PL), and 4-pyridoxic acid (PA)], and explored potential functional effects of the SNPs. Methods: Study subjects were young, healthy adults from Ireland ( n = 2345). We measured plasma PLP, PL, and PA with liquid chromatography–tandem mass spectrometry and genotyped 66 tag SNPs in the 4 genes. We tested for associations with single SNPs in candidate genes and also performed genome-wide association study (GWAS) and gene-based analyses. Results: Seventeen SNPs in ALPL were associated with altered plasma PLP in candidate gene analyses ( P < 1.89 × 10 −4 ). In the GWAS, 5 additional ALPL SNPs were associated with altered plasma PLP ( P < 5.0 × 10 −8 ). Gene-based analyses that used the functional linear model β-spline ( P = 4.04 × 10 −15 ) and Fourier spline ( P = 5.87 × 10 −15 ) methods also showed associations between ALPL and altered plasma PLP. No SNPs in other genes were associated with plasma PLP. The association of the minor CC genotype of 1 ALPL SNP, rs1256341, with reduced ALPL expression in the HapMap Northern European ancestry population is consistent with the positive association between the CC genotype and plasma PLP in our study ( P = 0.008). No SNP was associated with altered plasma PL or PA. Conclusions: In healthy adults, common variants in ALPL influence plasma PLP concentration, the most frequently used biomarker for vitamin B-6 status. Whether these associations are indicative of functional changes in vitamin B-6 status requires more investigation.